PS 07-08 ARGINASE II CONTRIBUTES TO REGULATION OF CaMK II-Dependent eNOS Activity Through Mitochondrial Ca2+ CHANNEL, P32. (September 2016) - Hwang, Hye Mi; Ryoo, Sungwoo
Abstract : Objective: Nitric oxide by endothelial nitric oxide synthase (eNOS) in endothelial cell is one of the most important elements to maintenance of vascular homeostasis. Arginase, an enzyme using the common substrate (L-arginine) with eNOS, synthesizes L-ornithine that is used for the synthesis of polyamines. In our previous study, we defined mitochondrial p32 protein as a Ca 2+ channel activated by spermine and regulates negatively cytosolic Ca 2+ level. Therefore, we investigated whether p32 protein regulates eNOS activity in the conditional arginase inhibition. Design and Method: Ca 2+ level was quantified by assessing fluorescent staining under microscope. Expression and phosphorylation of proteins in HUVEC/MAEC were analyzed by Western blots. Spermine concentration in wild type (C57BL/6J) and ArgII −/− mouse aorta was measured by HPLC. Vessel reactivity was tested by vascular tension assay. Results: Spermine increased mitochondrial p32 protein level in a concentration-dependent manner, which was associated with Ca 2+ translocation from cytoplasm to mitochondria and reduced phosphorylation of CaMKII (in HUVEC and MAEC). Down-regulation of mitochondrial p32 by antisense significantly enhanced CaMKII phosphorylation, resulted in increased eNOS Ser1177 phosphorylation. In ArgII −/− mouse aorta, spermine level was significantly lowered, which was responsible for the decrease in mitochondrial p32 protein expression, followed by a reduction of mitochondrial Ca 2+ concentration and elevated cytosolic Ca 2+ level in compared with WT mouse aorta. Treated p32 antisense and arginase II knock-out increase eNOS Ser1177 phosphorylation and decrease Thr495 phosphorylation. NO level was higher than WT, and improve vascular relaxation. Conclusions: We suggest a novel mechanism of eNOS activation through arginase activity-dependent p32 activation.